2021
DOI: 10.1038/s41598-021-91234-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for mortality in invasive pneumococcal disease in adult: a system review and meta-analysis

Abstract: Risk factors associated with mortality in invasive pneumococcal disease remain unclear. The present work is a meta-analysis of studies that enrolled only patients with invasive pneumococcal disease and reported on mortality. Potentially eligible reports were identified from PubMed, CHAHL, and Web of Science, comprising 26 reports in total. Overall mortality for invasive pneumococcal disease was reported as 20.8% (95% confidence interval (CI) 17.5–24%). Factors associated with mortality were age (odds ratio (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 38 publications
1
31
0
3
Order By: Relevance
“…Although the IPD incidence has decreased in the adult population, the elderly and adults with underlying medical conditions are carrying an increased proportion of the remaining IPD burden in several settings [ 3 , 4 , 5 , 6 , 7 ]. These high-risk groups also have an increased risk of IPD-associated mortality, highlighting the importance of adequate preventive efforts by vaccination [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the IPD incidence has decreased in the adult population, the elderly and adults with underlying medical conditions are carrying an increased proportion of the remaining IPD burden in several settings [ 3 , 4 , 5 , 6 , 7 ]. These high-risk groups also have an increased risk of IPD-associated mortality, highlighting the importance of adequate preventive efforts by vaccination [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…We examined the characteristics of IPDs in adults in our department. A systematic review and meta-analysis of IPD in adults by Chen et al 3) reported a mortality rate of 20.8%. They also reported that the factors associated with mortality were age, being in nursing home, nosocomial infections, septic shock, chronic diseases, solid organ tumor, immunosuppression, and alcohol abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The fatality rate of IPD in adults has been reported to be between 10-15% 2) . Recently, Chen et al conducted a systematic review and meta-analysis of the prognostic factors for mortality in adults 3) . Our study aimed to determine the clinical characteristics of IPD in adults by comparing it with pneumococcal pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 26 studies conducted in various countries reported the overall mortality rate due to IPD as 20.8%. Factors such as older age (>64 years old), septic shock, immunocompromising condition, underlying chronic diseases, solid organ tumors, alcohol abuse, nursing homes, and nosocomial infection were determined to be prognostic factors determining the mortality rate from IPD [ 7 ].…”
Section: Introduction—risk Of Pneumococcal Disease In Adultsmentioning
confidence: 99%